Russian Norm Entrepreneurship in Crimea: Serious Contestation or Cheap Talk? - Betcy Jose; Christoph H. Stefes (German Institute of Global and Area Studies (GIGA), 2018)
Western actors have long dominated the political processes and discourses that shape global norms impacting interstate behaviour. Yet, more recently, powerful autocratic regimes such as China and Russia have seemingly challenged democracies, emerging as potential contesters of international norms. What might be the outcome of this contestation? This paper broadly explores this query by investigating Russia's humanitarian justifications for its Ukrainian incursion. It examines whether Russia's claim of humanitarian intervention is more than a petty attempt to disguise pure power politics. Is Russia contesting Western understandings of humanitarian interventions in order to reshape our ideas of permissible violations of sovereignty norms to protect vulnerable populations? Using Atlas.ti, we also explore global responses to Russia's humanitarian claims. Our initial findings indicate that the Ukrainian intervention enabled Russia to contest Responsibility to Protect (R2P) and to champion an alternative version of humanitarian intervention with some limited success.
Keywords: 300; Russia; Crimea; authoritarianism; international norms; humanitarian intervention